Silviculture - Cristina Gonçalves, Ana (IntechOpen, 2021)
Silviculture is integral for the perpetuity and sustainability of forest stands and their yields. It encompasses several methods and techniques that make the bridge between individual trees and the stand. This book focuses on sustainable forest management with chapters on such topics as afforestation, thinning, pest control, and mitigation of climate change, among others.